COMPARISON OF OXYGEN ISOTOPE DATA OBTAINED BY LASER FLUORINATION OF OLIVINE WITH KRF EXCIMER LASER AND CO2 LASER - Farquhar J.; Rumble D. (My University, 1998)
The physics and chemistry of laser fluorination techniques that rely on CO2 lasers and excimer lasers differ on several fundamental levels: the mechanisms of laser-sample coupling, the time-scales of the interactions, and the nature of the fluorination chemistry. We examine the fluorination chemistry of the mineral olivine (Mg,Fe)2SiO4) and use the results of our laser fluorination analyses to assess the accuracy and precision of both techniques. Oxygen isotope analyses of two populations of olivine grains made by using the CO2 laser fluorination technique give δ18O of 5.02 and 4.84 ‰, respectively. Analyses of the same sample populations by KrF excimer laser give δ18O of 5.07 and 5.00 ‰, respectively. We maintain that these two techniques are independent of one another and, therefore, that these results can be used to confirm their respective accuracy and precision. We have also examined the chemistry of the two techniques for fluorination of olivine with an eye toward pinpointing pitfalls, advantages, and analytical strategies for each.